THE INFLUENCE OF ACCOUNTING DIGITALIZATION ON FINANCIAL REPORT EFFICIENCY IN INDONESIAN MIGRANT WORKERS' MSMES IN MALAYSIA - Sri Hartono; Titi Rapini; Umi Farida (Adisam Publisher, 2025)
This study aims to examine the effect of accounting digitalization on the efficiency of financial reporting in Micro, Small, and Medium Enterprises (MSMEs) managed by Indonesian Migrant Workers in Malaysia. The phenomenon of the increasing number of migrant workers running their own businesses abroad is an important highlight in the context of effective and efficient financial management. Using the literature review method, this study collects and analyzes various previous studies related to the implementation of digital technology in accounting practices, especially in the MSME sector. The results of the study indicate that accounting digitalization can have a positive impact on the efficiency of financial reporting by increasing the speed of recording, data accuracy, and ease of access and tracking of financial information. In addition, the adoption of digital technology is also considered to minimize the risk of manual errors and increase transparency in the reporting process. These findings contribute to the understanding of the importance of digital transformation in the financial management of MSMEs of Indonesian Migrant Workers abroad, as well as being the basis for the development of relevant policies and training.